One Day in Fremantle: TV representation of this alternative to Australia Day - Cox, Shaphan; Kerr, Thor (University of Barcelona, 2018)
A 2016 decision by the City of Fremantle in Western Australia to change its date of national celebration generated a televised controversy about the municipal observance of Australia Day. Beneath this controversy, Fremantle’s decision to change the date reflects a long ongoing struggle over the colonization of country belonging to Aboriginal and Torres Strait Islander peoples. This struggle can be traced back to the landing of the First Fleet of British settlers in Cadigal, Eora, country (Sydney) on 26 January 1788. This paper analyses the context of Fremantle’s decision and considers how television and current affairs reported it to audiences across Australia. Twenty-eight news and current affairs video recordings broadcast between 25 August 2016 and 29 January 2018 by ABC, Nine, NITV, Seven and SBS networks were analysed. Key themes emerging from this study are discussed, including: the emptiness and trouble with Australia Day representation; diversion through division and false economy; and, from genocide to solidarity with Aboriginal leadership. Finally, this paper offers an opportunity for understanding how Australian community has been imagined and how community in Australia could be imagined.